Exploring the relationship between eco-anxiety and suicide risk in adolescents with mental health disorders: insights from a cross-sectional observational study - Apolline Lerolle; Jean-Arthur Micoulaud-Franchi; Jean-Arthur Micoulaud-Franchi; Pierre Fourneret; Pierre Fourneret; Alexandre Heeren; Alexandre Heeren; Christophe Gauld; Christophe Gauld (Frontiers in Psychology)
IntroductionA limited number of studies have explored the connection between eco-anxiety, anxiety, and depression in adolescents. However, the relation between eco-anxiety and suicide remains unexamined. This cross-sectional observational study aims to bridge this gap by investigating the correlation between eco-anxiety intensity and suicide risk severity in adolescents.MethodsWe used validated French versions of the Climate Anxiety Scale (CAS) and its two key dimensions (cognitive and emotional and functional impairments), alongside the Columbia Suicide Severity Rating Scale (C-SSRS) and the Hospital Anxiety and Depression scale (HAD).ResultsOur study involved 87 hospitalized adolescent patients, aged 12–16. Although, the univariate model indicated a significant association between the CAS and the C-SSRS (β = 2.58; p = 0.049), the cognitive/emotional difficulties and functional impairment dimensions of eco-anxiety, considering different confounding factors, did not show statistical associations with the severity of suicide risk (respectively, p = 0.81 and p = 0.76).DiscussionIn an expansive literature, these results show for the first time that eco-anxiety may not be the priority of adolescents seen by adolescent psychiatrists. Such an observation would imply not overmedicalizing a dimension of life which perhaps does not fall solely within the field of medicine, but which concerns environmental issues broader than medical field. However, an ethical and prudent approach in mental health care for this particularly fragile population remains necessary. This intersection of eco-anxiety and suicide in youth opens up new avenues of research in the realm of environmental and mental health studies.